2010
DOI: 10.1523/jneurosci.4318-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Murine Embryonic Stem Cell-Derived Pyramidal Neurons Integrate into the Cerebral Cortex and Appropriately Project Axons to Subcortical Targets

Abstract: Although embryonic stem (ES) cells have been induced to differentiate into diverse neuronal cell types, the production of cortical projection neurons with the correct morphology and axonal connectivity has not been demonstrated. Here, we show that in vitro patterning is critical for generating neural precursor cells (ES-NPCs) competent to form cortical pyramidal neurons. During the first week of neural induction, these ES-NPCs begin to express genes that are specific for forebrain progenitors; an additional we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 46 publications
6
80
0
Order By: Relevance
“…These PSCs can be unlimitedly expanded and give rise to a wide variety of differentiated cells, making them a promising cell source for treating intractable neurological disorders, including Parkinson's disease [5][6][7] and ALS [8]. In fact, recent studies have shown that mouse [9] or human [10] ESC-derived neurons extend long axons from the motor cortex to the pyramidal tract in neonate mice. However, the efficiency to induce CMNs from ESCs or iPSCs is very low.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These PSCs can be unlimitedly expanded and give rise to a wide variety of differentiated cells, making them a promising cell source for treating intractable neurological disorders, including Parkinson's disease [5][6][7] and ALS [8]. In fact, recent studies have shown that mouse [9] or human [10] ESC-derived neurons extend long axons from the motor cortex to the pyramidal tract in neonate mice. However, the efficiency to induce CMNs from ESCs or iPSCs is very low.…”
Section: Introductionmentioning
confidence: 99%
“…In order to induce cortical neurons from mouse or human ESCs/iPSCs, serum-free embryoid body-like aggregates (SFEB) [11][12][13] or monolayer [9,10,[14][15][16][17] protocols are used. CMNs are located in the frontal/motor area of the anterior cortex, and the inhibition of Wnt signaling is important to induce this area.…”
Section: Introductionmentioning
confidence: 99%
“…By transplantation of dorsally patterned progenitors into postnatal murine cerebral cortex, the production of cortical projection neurons with the correct morphology and axonal connectivity has been demonstrated [98]. The pyramidal neurons express Otx1, Emx1, and Ctip2, corresponding to deep layers neurons.…”
Section: Neuronal Specificationmentioning
confidence: 99%
“…The pyramidal neurons express Otx1, Emx1, and Ctip2, corresponding to deep layers neurons. They integrate and appropriately project longdistance axons to subcortical targets, without forming tumors [98].…”
Section: Neuronal Specificationmentioning
confidence: 99%
“…40 Recently, it was demonstrated that ES cell-derived neural populations could generate dorsalized cortical phenotypes by antagonizing sonic hedgehog signaling. 41,42 Significantly, even cortical layer-specific phenotypes were generated, including GABAergic and glutamatergic neurons. After transplantation into neonatal or embryonic mice cortices, these cells showed an area-specific projection into corresponding thalamic nuclei (M1 to ventrolateral thalamic nucleus and S1 to ventrobasal).…”
Section: Cell Therapy Must Generate Lesion-specific Neuronal Phenotypesmentioning
confidence: 99%